Al-Magrizi Inflation Theory Of Islamic Monetary Policy Implementation In Indonesia - Ridan Muhtadi; Safarinda Imani (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2020)
During the time of Imam al-Magrizi (766-845 H), inflation had occurred in Egypt. Al-Magrizi shows about the theory of inflation. Inflation becomes a discourse that studied heavily in the subject of the economy. Al-Magrizi is an Islamic economic thought who did a particular study of money and inflation. The paper focused on al-Magrizi inflation theory caused by two factors, namely natural factors and human error factors. To solve these factors, a nation could apply Islamic monetary policy to Umar Chapra's thought, namely a credit-oriented (financing) location as a solution of natural factor theory. Also, moral suasion or moral appeals as a solution to the human factor inflation theory.